Plantar loading in the youth soccer player during common soccer movements and risk for foot injury. Issue 8 (August 2020) - Azevedo, Renato R; Nery, Suellen B; Stefanyshyn, Darren J; Carpes, Felipe P
Highlights: Young soccer players show high plantar pressure in the forefoot. Fifith metatarsal of youth players experiences higher pressure during soccer. Footwear can be manipulated to reduce pressure in the youth players. Abstract: Introduction: Soccer players are at high risk of stress injuries in the foot. While most research addresses this issue in professional athletes, there is little information concerning young athletes. As soccer is practiced around the world since early infancy, we set out to determine whether young soccer athletes are susceptible to increased foot loading that increase risk factors for foot injuries in a similar manner as reported by the literature to the adult athlete. Methods: twenty-six male adolescents (mean age 16 years old) were organized into two groups: soccer players ( n  = 13) and controls ( n  = 13). Groups were compared regarding foot sensitivity, ankle range of motion, Q-angle, and plantar pressure determined during running and cutting movements performed at maximal speed and using different shoes. Results: Foot sensitivity, ankle range of motion and Q-angle did not differ between the groups. During performance of soccer actions, young players showed higher peak pressure in the lateral region of the foot including the fifth metatarsal region. These higher peaks were minimized by manipulation of the footwear. Conclusion: In summary, young soccer athletes show dynamic plantar pressure patterns that are related to foot injury in the adult athlete, and this condition can be minimized by the manipulation of the footwear. Additional attention should be paid to the young athlete in soccer aiming to minimize long-term risk for stress injuries in the foot.